2014
DOI: 10.1177/2050640614530919
|View full text |Cite
|
Sign up to set email alerts
|

Challenging the dogma: a randomized trial of standard vs. half‐dose concomitant nonbismuth quadruple therapy for Helicobacter pylori infection

Abstract: Background: Current treatment of Helicobacter pylori consists of three or four drugs for 7-14 days with important associated cost and adverse events. Aims: This study compared efficacy and safety of standard dose vs. half-dose concomitant nonbismuth quadruple therapy (NBQT) for 7 days. The standard dose consisted of twice daily rabeprazole 20 mg, amoxicillin 1 g, metronidazole 500 mg, and clarithromycin 500 mg. Methods: This was a prospective randomized trial.14 C-urea breath test was performed !4 weeks after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Eighteen studies included the classical triple therapy with a proton pump inhibitor (PPI), amoxicillin and clarithromycin, and two studies had metronidazole instead of amoxicillin in the triple therapy. One study included nonbismuth concomitant quadruple therapy with a PPI, amoxicillin, metronidazole and clarithromycin . Similarly, sequential therapy with PPI and amoxicillin followed by PPI, clarithromycin and tinidazole was included in one study only .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighteen studies included the classical triple therapy with a proton pump inhibitor (PPI), amoxicillin and clarithromycin, and two studies had metronidazole instead of amoxicillin in the triple therapy. One study included nonbismuth concomitant quadruple therapy with a PPI, amoxicillin, metronidazole and clarithromycin . Similarly, sequential therapy with PPI and amoxicillin followed by PPI, clarithromycin and tinidazole was included in one study only .…”
Section: Resultsmentioning
confidence: 99%
“…repeated the analysis after including one additional RCT of 352 patients and found no significant difference in the 500 mg dose of clarithromycin in amoxicillin‐containing triple regimen . As a large number of additional studies have addressed this question, the evidence from these individual trials suggests that half‐dose clarithromycin may be equally effective to standard full‐dose therapy, but is associated with less costs and side effects . In this systemic review and meta‐analysis, we review all the studies published to date with the aim of assessing the safety and efficacy of half‐dose vs. full‐dose clarithromycinin H. pylori treatment.…”
Section: Introductionmentioning
confidence: 99%
“…18 In another prospective randomized trial, researchers reduced the dosage of all druges (rabeprazole, amoxicillin, clarithromycin, and metronidazole) by 50%, and achieved a similar conclusion. 19 Moreover, a research based on patients with end-stage renal disease also showed that a 50% reduction in clarithromycin did not diminish the treatment efficacy (74% vs 74%). 20 However, most of the regimens involved are triple therapies.…”
Section: Introductionmentioning
confidence: 98%
“…In one meta‐analysis, researchers assessed efficacy of full‐ and half‐dose clarithromycin‐based triple therapy and suggested to use half‐dose clarithromycin for the treatment of H.pylori infection infections . In another prospective randomized trial, researchers reduced the dosage of all druges (rabeprazole, amoxicillin, clarithromycin, and metronidazole) by 50%, and achieved a similar conclusion . Moreover, a research based on patients with end‐stage renal disease also showed that a 50% reduction in clarithromycin did not diminish the treatment efficacy (74% vs 74%) .…”
Section: Introductionmentioning
confidence: 99%
“…Recent meta-analyses have consistently shown its advantage over triple therapy. 33,34 In addition, several recent studies over the last 4 years 18,19,35-50 evaluating the efficacy of concomitant therapy have been conducted in Latin America, 35 Asia (Thailand, 36 Japan, 37 Taiwan, 38,39 China, 40 and Korea 19,41,42 ), and Europe (Spain, [43][44][45] Greece, 46,47 Italy, 48,49 and Turkey 18,50 ). Regardless of the duration of therapy, all studies showed intention-totreat cure rates ranging between 85% and 94%, with the exceptions of regions where dual resistance is high (Turkey 18 and Korea 19 ) or where the duration of therapy tested was possibly too short (5 days in Latin America 35 and Korea 37 ).…”
Section: Concomitant Therapymentioning
confidence: 98%